SLEEP ON MONEY? A TAM-BASED STUDY ON THE ADOPTION INTENTION OF OPEN BANKING IN TAIWAN - Yu-An, Wu; Ai-Che, Chang (PEOPLE: International Journal of Social Sciences, 2025)
Although Taiwan has promoted Open Banking policies and technologies, the penetration of these services remains relatively low. Understanding the factors that influence adoption intention is crucial to developing more user-oriented services. While prior research on Open Banking has primarily focused on technical feasibility and regulatory frameworks, studies from the consumer perspective are still limited. This study applies the Technology Acceptance Model (TAM) and incorporates perceived risk as an external factor to examine what drives or inhibits Open Banking adoption among Taiwanese consumers. A total of 290 valid responses were collected via an online survey. Path analysis was conducted using partial least squares structural equation modeling (PLS-SEM). The results indicate that most of the core TAM constructs exhibit significantly positive correlations, supporting the model’s explanatory power. Among six dimensions of perceived risk, only Psychological Risk exhibits significant negative influence, suggesting that lack of confidence or not align with user habit may reduce adoption intention. The findings provide practical implications for both supervisors and financial institutions. Enhancing consumer education and improving user experience (UX) design will help alleviate concerns and build trust, thereby advancing wider adoption of Open Banking services.